A Review of Lithium‐Ion Battery Electrode Drying: Mechanisms and Metrology. Issue 2 (28th November 2021) - Zhang, Ye Shui; Courtier, Nicola E.; Zhang, Zhenyu; Liu, Kailong; Bailey, Josh J.; Boyce, Adam M.; Richardson, Giles; Shearing, Paul R.; Kendrick, Emma; Brett, Dan J. L.
Abstract: Lithium‐ion battery manufacturing chain is extremely complex with many controllable parameters especially for the drying process. These processes affect the porous structure and properties of these electrode films and influence the final cell performance properties. However, there is limited available drying information and the dynamics are poorly understood due to the limitation of the existing metrology. There is an emerging need to develop new methodologies to understand the drying dynamics to achieve improved quality control of the electrode coatings. A comprehensive summary of the parameters and variables relevant to the wet electrode film drying process is presented, and its consequences/effects on the finished electrode/final cell properties are mapped. The development of the drying mechanism is critically discussed according to existing modeling studies. Then, the existing and potential metrology techniques, either in situ or ex situ in the drying process are reviewed. This work is intended to develop new perspectives on the application of advanced techniques to enable a more predictive approach to identify optimum lithium‐ion battery manufacturing conditions, with a focus upon the critical drying process. Abstract : This paper provides a comprehensive review of the drying effects on the lithium‐ion battery electrodes with a critical discussion about the drying mechanism. The existing and emerging metrology are also covered with the discussion of current challenges. The future research direction is identified which provides an outlook of this field, that substantially can benefit the lithium‐ion battery manufacturing process.